Agricultura urbana e identidade: mecanismos e dinâmicas para a transformação do urbano e dos sujeitos no Sistema Agroflorestal Odara em Itapetininga, São Paulo. - Carpigiani, Pedro Henrique Carvalho (2023)
There are several actions in which we strive to make cities viable and sustainable, pursuing to be an alternative to the actual problems in the daily life of urbanization. In this dissertation, one of these alternatives is presented, urban agriculture (UA), which aggregates diversified practices aimed at self-consumption and/or sale to urban local markets. It occurs in distinct areas, in terms of size, location and land ownership, whether public or private. This paper focuses on pointing out that UA practices happen informally, spontaneously and in different localities. UA techniques such as soil management, vegetable and animal farming which have been incorporated into the concept are not new in the urban environment, but in the academic and institutional environment this subject is a novelty. Thereby, the objective of this work is: To analyze how the Agroforestry System Odara becomes a mechanism for the development of ecological subjects through the transformation of urban space. The data were collected through semi-structured interviews carried out with the Odara Group, residents at the surroundings of the Odara AFS and, the public power of the municipality of Itapetininga. With this dissertation, it is concluded that urban agriculture plays an important role in shaping an ecological subject, contributing to awareness and social transformation regarding environmental issues.